Effects of Jigsaw-puzzle and Graphic Organizer Instructional Strategies on Biology Students’ Performance in Abia State - Joy C. Chukwu; J. W. Dike (Archives of Current Research International, 2019)
The study investigated the effects of jigsaw-puzzle and graphic organizer instructional strategies on Biology students’ performance in Ukwa West Local Government Area, Abia State. Three groups pre-test post-test control group non-equivalent quasi-experimental design was employed in the study. Two objectives, two research questions and two hypotheses guided the study. One hundred and fifty-one (151) senior secondary school one (SSS1) students out of a total population of 450 Biology students formed the sample size of the study. Biology Performance Test on growth (BPTOG) was used for gathering data. The instrument was tested using test re-test method and was validated by two experts in the Department of Curriculum Studies and Educational Technology, University of Port Harcourt, Nigeria. A reliability index of 0.75 was obtained using Pearson’s Product Moment Correlation. The data was analyzed using mean and standard deviation to answer the research questions while analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The result of the study showed that Jigsaw-Puzzle and Graphic Organizer are effective instructional strategies for enhancement of students’ academic performance in growth as a concept in Biology. It was recommended that Biology teachers should adopt Jigsaw-Puzzle and Graphic Organizer Instructional Strategies to teach the concept of growth in the class.